Dorsal root ganglia volume differentiates schwannomatosis and neurofibromatosis 2 - Godel, Tim; Schwarz, Daniel; Kronlage, Moritz; Heiland, Sabine; Bendszus, Martin; Bäumer, Philipp (Annals of neurology, 2018)
Schwannomatosis and neurofibromatosis type 2 are hereditary tumor syndromes, and peripheral neuropathy has been reported in both. We prospectively applied in vivo morphometric measurement of dorsal root ganglia volume in 16 schwannomatosis patients, 14 neurofibromatosis type 2 patients, and 26 healthy controls by magnetic resonance neurography. Compared to healthy controls, dorsal root ganglia hypertrophy was a consistent finding in neurofibromatosis type 2 (L3, + 267%; L4, + 235%; L5, + 241%; S1, + 300%; S2, + 242%; Bonferroni-adjusted p < 0.001) but not in schwannomatosis. Dorsal root ganglia may be a vulnerable site in origination of areflexia and sensory loss and a useful diagnostic marker in neurofibromatosis type 2.
Gesehen am 08.05.2019